Pictures for the sky famous artists design kites. (Northbrook, Ill. Roland Collection, 1993)
"Working in conjunction with Japanese master kite-makers, a hundred famous artists from twenty countries all over the world created 'art kites' to turn the sky above Himeji, Japan into a playground for their world of paintings." - Roland Collection"
VHS format.
Director / script, Markus Zollner ; original sound, Jan Kollwitz.
Keywords: Kites -- Exhibitions